Time-dependent reliability assessment of offshore jacket platforms. (17th August 2016) - Bai, Yong; Yan, Hui-bin; Cao, Yu; Kim, Younghoon; Yang, Yong-yan; Jiang, Hua
Abstract : The reliability assessment method has been developed into a widely used method to conduct safety assessment of jacket platforms. Traditionally, the structural resistance is considered to be a constant during the design reference time. However, platform structures degrade over time. Therefore, a reliability assessment method that considers the resistance degradation will be better suited. A time-dependent reliability assessment of the offshore jacket platform was studied in this paper. The base shear capacity was considered as the resistance of the platform. For the resistance probability model of the jacket platform, the corrosion effect was considered for the degradation of the resistance. A proper corrosion model was studied. For the load effect probability model, the typhoon load effect, containing wind, wave and current loads, was used. At last, an example platform was studied using the proposed method and the results showed that the method could be used in practical engineering applications.